(untitled) (Bulletin of Innovative Research, 2026)
This article analyzes the characters in Zulfiya Kurolboy’s novel "The Difficult Paths of Life." A scholarly analysis and comparison is provided of the character of a lawyer, the character of a woman, and the character of public life. The quality of a person’s character and the skill of character creation are determined based on their profession.